A feasibility study of BandaRito the first gig finder in the Philippines - Vistal, Reuel John G.; Cruz, Edison (Quezon City University of the Philippines Diliman, 2016)
The study discusses the scope, platform features, and the viability of BandaRito as a business. BandaRito is a web application that integrates several social networks into one so that music enthusiasts and fans would no longer need to visit different social media platforms. Because bands promote themselves in various sites, it has been a challenge for fans and music enthusiasts to follow them. BandaRito aims to create a one-stop plaftform where music enthusiasts can visit and have all the information they desire about their favorite artists. The study covers bands who perform within the vicinity of Metro Manila and music enthusiasts who reside in Metro Manila or in the nearby provinces.

Digital music has started to take over the world. A 10.5 percent increase in digital revenues was experienced last year, overtaking physical formats. The increase in revenues accounts for more than 6.7 billion dollars. The International Federation of the Phonographic Industry reports that digital sales through online platforms has helped the increase the music industry's profit by 3.2 percent. All of this is accounted by the enormous growth of the use of social media platforms. Companies have switched from traditional marketing media to social networking sites to market their products. Following this move, bands have used this platform to market themselves and their music. Social media platforms create an environment where bands can interact with their fans usually in real time. This has worked for and against artists like bands. The existence of social media accounts has opened not only their music but their lives to everyone. Because of this, anything they post online is to subject to public opinion.

BandaRito is an integration of different social media platforms in the form of a web application. What makes web applications different from websites is that they focus more in carrying different tasks by making processes easier and faster. In order to achieve the goal of BandaRito, the researcher enumerated the important functions that the platform contains : a.) Gig Finder/Search, b.) Profile Page, c.) Image, Video and Music Sharing, d.) Band Directory/ Listing, e.) Locator and f.) Live Chat

As part of the study's technology analysis, the technical requirements are summarized into three : programming language to use, web hosting, and manpower for development and maintenance. The biggest consideration in choosing the programming language to use and for hiring developers are cost and availability of experienced developers. For web hosting, cost and scalability are deemed very important. For the platform's development, the procurement options were narrowed down to either outsourcing or do in-house development.

The study uses Michael Porter's Five Forces to study the business idea's competitive position. Threat of New Entry, Competitive Rivalry, Supplier Power, Threat of Substitution, and Buyer Power were the factors used to determine the competitive strength of BandaRito against the current competitive landscape of the industry. The study uses a qualitative research method called focus group discussion (FGD). One group of selected bands and another for music enthusiasts were gathered and were asked to give their opinions and thoughts about a set of questions. The general objectives of the FGDs are to verify the study's assumptions, gather information regarding the current platforms, and lastly, to verify if there's a need for a platform like BandaRito and how it can solve the participants' current problem.

The study presents the results of the FGDs gathered from the bands and music enthusiasts. The data gathered from the discussions and other available information are analysed using Porter's Five Forces Model. The researcher also studied the market it intends to capture by segmenting its customers, identifying its target market, and positioning the proposed value to its potential customers. To further narrow down its targeted customers, the study determines the characteristics of the targeted market and its market size. Lastly, the researcher enumerates the value proposition of the business and how it can be positioned to its target market.

The researcher was able to get insights from the FGD participants. They validate the assumptions of the research such as the existing problem of music enthusiasts in dealing with different platforms to follow their favorite bands. Also, the participants were able to give the researcher information regarding which social media platforms they use, including the pros and cons of using them. Lastly, the researcher was able to ask the participants what they think if a one-stop platform were to exist and what kind of features they think it should have.

The researcher uses the Network Subscription model which charges bands a monthly subscription fee of PhP200.00 per month for a premium account. Bands can opt for a free account but with a limited number of features that can be used within the platform. Bands with premium accounts have access to different features like live chat, check-in, original content upload, and huge video and image uploads space to be shared with the fans. The platform offers free use to all music enthusiasts and fans.

As part of the business model, the researcher lists down a set of marketing strategies in order to get the word out in the open and get people to use BandaRito. One of the strategies is to offer premium services for the first two months for new users. This would give consumers the opportunity to try the benefits of a premium account. Partnership with different music organizations and managements would promote the business to musicians. Traditional strategies like discount and promo codes will also be used to encourage people to visit and sign up.

Finally, the study examines the financial feasibility of the business idea by looking at the capital cost and strategy, one-time and recurring operational costs, and a cash flow forecast using the bottom-up approach. The initial capital to start the business is projected to be PhP150,000.00. Majority of this will be used to pay for the upfront costs and the first few months of the recurring costs. The business capital will be raised through bootstrapping. Finally, it is expected to have this amount returned in 22 to 24 months of operation with at least 55 monthly subscribers.
In partial fulfillment of the requirements of TM 299
Thesis
Keywords: Web applications; Band musicians; Gig Finder